2014
DOI: 10.1164/rccm.201310-1827oc
|View full text |Cite
|
Sign up to set email alerts
|

CCL17 Production by Dendritic Cells Is Required for NOD1-mediated Exacerbation of Allergic Asthma

Abstract: Data from this study unveil a deleterious role of NOD1 in allergic asthma through direct induction of CCL17 by dendritic cells, arguing for a need to address vaccine formulation safety issues related to allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…Pulmonary DCs were also highly elevated in Tlr4 -mutant mice in an allergic inflammation model, which supports our study, as well as several inflammatory markers typically increased by activated DCs in lungs of BALB Lspd mice treated with BHT, such as costimulatory molecule (CD40, data not shown) and Ccl17 (Tarc) (Fig 7) (42, 54, 55). The DCs can also lead to NK cell activation, which we observed increased cell numbers, with potential to secrete cytokines/chemokines that activate specific types of macrophages (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pulmonary DCs were also highly elevated in Tlr4 -mutant mice in an allergic inflammation model, which supports our study, as well as several inflammatory markers typically increased by activated DCs in lungs of BALB Lspd mice treated with BHT, such as costimulatory molecule (CD40, data not shown) and Ccl17 (Tarc) (Fig 7) (42, 54, 55). The DCs can also lead to NK cell activation, which we observed increased cell numbers, with potential to secrete cytokines/chemokines that activate specific types of macrophages (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…At sacrifice, lungs were ½ lung bronchoalveolar lavaged (42) with Hanks Balanced Salt Solution (HBSS) with ethylenediaminetetraacetic disodium salt (EDTA) to determine immune cell constituents using cellular differentials in the BAL fluid (BALF), as done previously (29). For flow cytometry, the lavaged right lung was minced and digested with 1 mg/ml collagenase (43) at 37°C for 30 min (44).…”
Section: Methodsmentioning
confidence: 99%
“…21,34 CCL17 was not only released from DCs but also promoted the maturation of DCs via a positive feedback to enhance the polarization of Th2 cells. 35,36 Knock-down of CCL17 during the maturation of DCs decreased the recruitment of CD4 + T cells and Tregs. 37 Reports showed that the interaction of RSV and Th2 cytokines tends to induce the expression of CCL17 via NF-κB and STAT6 pathway respectively.…”
Section: Discussionmentioning
confidence: 99%
“…NOD1-primed human DCs polarize naive T cells toward a Th2 profile, favoring allergic exacerbations, and this is due to the induction of CCL17 (chemokine pro-Th2). Vaccine formulations that engage NOD1 could contribute to increasing allergic asthma [100] …”
Section: Immunology and Lung Diseasesmentioning
confidence: 99%